PREVENTIVE DETENTION AND PRISON OVERCROWDING IN MOROCCO: AN INADEQUACY IN SEARCH OF A SOLUTION - Jaouhar, Mohamed (2024)
For several years, prison overcrowding has been a serious problem in Moroccan prisons. Its constancy results from prison inflation which is only progressing and a disproportionate volume of preventive detention. The statistics published annually by the prison administration are very alarming and clearly show the extent of this inadequacy, both in terms of stock and in terms of flows. Prison overcrowding is the essential result of excessive use of preventive detention by the judicial authorities, but also of the cumbersomeness of the judicial machine in the processing of criminal cases. This correlation between preventive detention and prison overcrowding can really impact the management of prison space and annihilate the reintegration efforts deployed by the prison administration. Overcrowding can only lead to a deterioration of detention conditions, and therefore have a negative impact on the human rights of detainees and constitute a violation of constitutional guarantees. This situation was criticized by various national authorities, who denounced the persistence of prison overcrowding and the excessive use of preventive detention, and who called for reforms. In our opinion, inadequacy is not inevitable, because various criminal measures can constitute avenues for resolving the inadequacy.